ANALISIS PENDAPATAN PETANI AGROFORESTRI TRADISIONAL DUSUNG DI NEGERI HATU (SERAM SELATAN) KECAMATAN TEHORU KABUPATEN MALUKU TENGAH - Maikel Walalayo; Jan Willem Hatulesila; Mersiana Sahureka (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
Agroforestry, commonly referred to as wanatani in Indonesia, can be simply defined as the practice of planting various types of trees on agricultural land, typically carried out by farmers. Agroforestry studies are not only analyzed from technical and biophysical aspects but also from socio-cultural and economic perspectives. This study examines the traditional agroforestry system, particularly the dusung farming pattern that combines forestry and agricultural crops in Negeri Hatu, Central Maluku Regency. The purpose of this research is to determine the income of farmers practicing the dusung agroforestry pattern and to identify the factors influencing their earnings. Data collection in the field was conducted using purposive sampling. The characteristics of respondents managing dusung agroforestry systems were determined based on age, education level, land area, number of land units, and land ownership status, ensuring they represented the target farmer population for the study. The results of the study showed that the income of agroforestry farmers in the hamlet in Negeri Hatu was Rp 353,955,000,-, but the per capita income per month was only Rp. 14,211 below the Provincial Minimum Wage. Three factors that affect the income of agroforestry farmers in the hamlet in Negeri Hatu are land area, production costs, and market prices.